Improving students' reading comprehension skills through the survey, question, read, recite, review (SQ3R) method - Samuel Sinulingga; Erikson Saragih; Christin Agustina Purba (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research describes the development of the ability to understand reading content and student activity when learning using the SQ3R method at XII APT SMK Negeri 1 Panai Hulu T.P 2022/2023. They used two cycles for 16 weeks in Odd Semester. The results of 2 rounds of research obtained the following: 1. Reading Skills Students' comprehension improves by using the SQ3R method. A mean of 65 was obtained during the first ability test, with a final classical percent of 45%. And in the second ability test, a mean result of 85 was obtained with a final class percentage of 87%, and 31% progress was obtained. The result was an increase, and a minimum requirement of the Indonesian language was achieved. 2. There is an increase in students' activities in absorbing teaching materials by applying the SQ3R method.